A Self-Consistent-Field Perturbation Theory of Nuclear Spin Coupling Constants - Blizzard, Alan Cyril (My University, 1972)
The principal methods of calculating nuclear spin coupling constants by applying perturbation theory to molecular orbital wavefunctions for the electronic structure of molecules are discussed. A new method employing a self-consistent-field perturbation theory (SCFPT) is then presented and compared with the earlier methods. In self-consistent-field (SCF) methods, the interaction of an electron with other electrons in a molecule is accounted for by treating the other electrons as an average distribution of negative charge. However, this charge distribution cannot be calculated until the electron-electron interactions themselves are known. In the SCF method, an initial charge distribution is assumed and then modified in an iterative calculation until the desired degree of self-consistency is attained. In most previous perturbation methods, these electron interactions are not taken into account in a self consistent manner in calculating the perturbed wavefunction even when SCF wavefunctions are used to describe the unperturbed molecule. The main advantage of the new SCFPT approach is that it treats the interactions between electrons with the same degree of self-consistency in the perturbed wavefunction as in the unperturbed wavefunction. The SCFPT method offers additional advantages due to its computational efficiency and the direct manner in which it treats the perturbations. This permits the theory to be developed for the orbital and dipolar contributions to nuclear spin coupling as well as for the more commonly treated contact interaction. In this study, the SCFPT theory is used with the Intermediate Neglect of Differential Overlap (INDO) molecular orbital approximation to calculate a number of coupling constants involving 13c and 19F. The usually neglected orbital and dipolar terms are found to be very important in FF and CF coupling. They can play a decisive role in explaining the experimental trend of JCF among a series of compounds. The orbital interaction is found to play a significant role in certain CC couplings. Generally good agreement is obtained between theory and experiment except for JCF and JFF in oxalyl fluoride and the incorrect signs obtained for cis JFF in fluorinated ethylenes. The nature of the theory permits the latter discrepancy to be rationalized in terms of computational details. The value of JFF in difluoracetjc acid is predicted to be -235 Hz. The SCFPT method is used with a theory of dπ - pπ bonding to predict in agreement with experiment that JCH in acetylene will decrease when that molecule is bound in a transition metal complex.
Scope and Content stated in the place of the abstract.
Keywords: nuclear spin coupling constants, perturbation theory, molecular orbital wavefunctions, self-consistent-field (SCF), electron interactions, computational efficiency, SCFPT theory